PENGARUH PEMBINAAN DAN PELATIHAN TERHADAP PENINGKATAN KREATIVITAS PENGRAJIN BATIK DI KABUPATEN INDRAGIRI HULU - Riandi Ilham Pandi; Hendriani Susi; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of coaching and training on Increasing the creativity of batik craftsmen in Indragiri Hulu Regency. The population in this study included all employees/craftsmen in the industry in Indragiri Hulu Regency, totaling 30 people. Primary data was collected with a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study was to use path analysis (path analysis) with the help of the SPSS(Statistical Program For Social Sciences). The sampling technique that has been chosen is the census method (30 industrial employees / batik craftsmen in Indragiri Hulu Regency. The results showed that: 1) there was a positive and significant effect of coaching on increasing creativity in industry in Indragiri Hulu Regency, 2) there was a positive and significant effect of training on increasing creativity in industry in Indragiri Hulu Regency.Keywords: coaching, training, creativity